2023
DOI: 10.1002/slct.202300220
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Origin and Therapeutic Implications of Benzopyran and Its Derivatives

Abstract: Benzopyran derivatives are essential for life and are found abundantly in nature. Benzopyran compounds and their derivatives play an essential role in medicinal chemistry. The alkaloids, flavonoids, tocopherols, and anthocyanins natural products comprise benzopyran's basic structure. Various benzopyran derivatives have been used for therapeutic effects. Benzopyran derivatives can be proficient in various pharmaceutical applications for cellular markers. The basic structure of benzopyran is an efficient class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 155 publications
(209 reference statements)
0
3
0
Order By: Relevance
“…In addition, a portion of the LU of CBN was removed with the goal of decreasing the molecular weight and lipophilicity of the CBN analogs because these two molecular properties are the most important factors in influencing the pharmacokinetics and pharmacodynamics of drug candidates [ [22] , [23] , [24] ]. Instead, a simplified version of the benzopyran ring system as the LU was designed in order to retain the structural rigidity and relevant bioactivity [ 25 , 26 ]. Following our previously reported protocol with modifications [ 12 ], combinatorial chemistry was then performed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a portion of the LU of CBN was removed with the goal of decreasing the molecular weight and lipophilicity of the CBN analogs because these two molecular properties are the most important factors in influencing the pharmacokinetics and pharmacodynamics of drug candidates [ [22] , [23] , [24] ]. Instead, a simplified version of the benzopyran ring system as the LU was designed in order to retain the structural rigidity and relevant bioactivity [ 25 , 26 ]. Following our previously reported protocol with modifications [ 12 ], combinatorial chemistry was then performed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the newly designed analogs contains the CU + RU derived from either olivetol or 5-(1,1-dimethylheptyl)resorcinol, the two best 5-alkylbenzene-1,3-diols identified in the screening of fragment compounds ( Table 1 ). In addition, a simplified version of the benzopyran ring system was included as the LU in order to retain the structural rigidity and relevant bioactivity of CBN [ 25 , 26 ]. In silico pharmacokinetic evaluation with the SwissADME tool suggested that these four analogs generally possess better CNS druglike properties than CBN in terms of smaller molecular weights, a better balance of lipophilicity/hydrophilicity and BBB permeability ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SWNTs are synthesized from virgin LD-PE and PP plastics. [105] LD-PE and PP are pyrolyzed at between 370 to 550 °C ranges, [105][106][107][108][109][110][111][112][113][114][115] which is determined by TGA. The high quality of the SWNTs was found with an oxidation peak at 588 °C while the oxidation of graphite flakes that a shoulder peak between 400 to 500 °C, which encapsulates the MgO supported by a catalyst-free approach during the CVD process.…”
Section: Analyzed Cnts Materialsmentioning
confidence: 99%